Clustering the Portuguese population regarding adoption and intention to use UAM - Prazeres, Duarte Mota Poseiro Rodrigues (2022)
With the growing use of public transport, the means that currently exist become insufficient and incapable of meeting the needs of the population, giving rise to the urgent need to develop a new means of mobility. From the investment in technologies such as automation, a concept emerges that involves circulation in the airspace of cities, Urban Air Mobility which can be used for both passenger and freight transport and proves to be a more sustainable option to respond to mobility needs of citizens. This study seeks to find out in the Portuguese population which groups will be more receptive to embrace this new form of mobility, through the levels of acceptance and intention to use air vehicles. Data collection is done using an online survey, where respondents are presented with various factors that may impact how they will accept or use the technology when it is implemented, determining factors such as safety, mobility habits, environmental impact, or possible benefits or disadvantages of its application. The survey was distributed in Portugal and valid 485 responses were obtained, the collected data was applied in order to develop a cluster analysis, preceded by a principal component analysis to ensure a more concrete division of groups, and also non-parametric analyses. This study intends to understand which groups within the Portuguese population will be more open to receiving UAM as a reliable means of transport and which factors are nuclear to the acceptance of this technology.